2021
DOI: 10.3389/fonc.2021.618793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PRM1201 Combined With Adjuvant Chemotherapy on Preventing Recurrence and Metastasis of Stage III Colon Cancer: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: BackgroundChemotherapy is the standard adjuvant treatment for colon cancer. Chinese herbal formula PRM1201 improves the efficacy of chemotherapy when used in combination with Cetuximab or Bevacizumab in patients with metastatic colorectal cancer. This study aims to explore the benefits of treatment with chemotherapy plus PRM1201 in the postoperative adjuvant setting.MethodsIn this parallel-group study, patients who had undergone curative resection for stage III colon cancer were randomly assigned to receive ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Surveys indicate that approximately 80 percent of patients in China had used TCM, particularly CHM, during cancer treatment [ 48 , 49 ]. Mounting evidence, meanwhile, suggests that Chinese medicine prescriptions have significant effect of colon cancer progression control [ 16 , 20 , 50 53 ]. XLJDOD is an empirical prescription used as an adjuvant treatment of colorectal cancer for more than 10 years in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys indicate that approximately 80 percent of patients in China had used TCM, particularly CHM, during cancer treatment [ 48 , 49 ]. Mounting evidence, meanwhile, suggests that Chinese medicine prescriptions have significant effect of colon cancer progression control [ 16 , 20 , 50 53 ]. XLJDOD is an empirical prescription used as an adjuvant treatment of colorectal cancer for more than 10 years in China.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study indicated that adherence to medication of TCM after surgery could significantly improve disease-free survival in colorectal patients with stage III disease [ 19 ]. Furthermore, a randomized controlled trial of 370 patients showed that Chinese herbal formula composed of seven herbs (PRM1201) in combination with adjuvant chemotherapy in the treatment of stage III colon cancer could effectively increase the 3-year DFS rate and improve their life quality [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“… 8 More and more studies have confirmed that TCM can enhance anti-tumor effects by regulating the immune system. 9 , 10 The aim of this study is to introduce how immune cells and non-immune cells in TME promote tumor progression, and to summarize the research progress of TCM in regulating TME.…”
Section: Introductionmentioning
confidence: 99%
“…A pioneering study arranged CRC survivors into clusters by four emotion regulation patterns and suggested that health care professionals should be aware of the individual differences in the emotions of these CRC patients [ 7 ]. Our previous randomized controlled clinical study in CRC showed that disease-free survival was negatively correlated with worse emotional function [ 8 ].…”
Section: Introductionmentioning
confidence: 99%